Factors affecting the probability of double brooding by Southern House Wrens - Carro, Mariana Emilia (2014)
Seasonal fecundity of birds is influenced by clutch sizes and the number of successful breeding attempts during a breeding season. As such, understanding the factors that determine the decision to initiate multiple broods within a season and the consequences of this reproductive tactic is important. We examined the frequency of double brooding by Southern House Wrens (Troglodytes aedon musculus) in eastern Argentina. We analyzed inter- and intraseasonal variation in double brooding and evaluated the effect of weather conditions and laying date on the frequency and occurrence of this behavior. Finally, we assessed the effect of double brooding on the seasonal and lifetime productivity of female Southern House Wrens. During our 8-year study, we found that ∼43% (range = 17–83% each year) of breeding pairs attempted a second brood after successfully raising a first brood. The probability of females having a second brood was affected by the laying date of the first nesting attempt, but was independent of the number of young fledged. About 65% of females that started laying eggs before the first quarter of each breeding season produced a second brood, and this percentage decreased to ∼40% after this period. In addition, variation in double-brooding frequency among years was related to weather conditions, with the proportion of pairs double brooding increasing with increased precipitation early in the breeding season. More precipitation likely contributed to an increase in insect abundance. Although double brooding increased the seasonal and lifetime productivity of female Southern House Wrens, additional study of the survival and fate of fledglings from first and second broods is needed to assess the importance of multi-brooding in the reproductive success of these wrens.